A nondifferentiable semigroup generated by a model of cell population dynamics - Arino, Ovide; Kimmel, Marek (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we are concerned with regularity of operator semigroup generated by population models defined by functional-integral equations. Contrary to the semigroups defined by functional-differential equations, our semigroups do not necessarily become increasingly more regular with time. We furnish an example of a special case of a cell population model which generates a nondifferentiable semigroup.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka